KAJIAN INTERAKSI OBAT PADA PASIEN KANKER LEHER RAHIM (Serviks Uteri) RAWAT INAP DI RSUP Dr. KARYADI SEMARANG TAHUN 2007 - ibrahim arifin; nurul latifah; mustofa mustofa (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2008)
ABSTRACTCervical uterine cancer is a deadly tumor attacking the cervix uteri. In Indonesia, cervix uteri cancer constitutes the most aggresive and deadly cancer. Frequently, combinations of several different drugs are used for treating this disease. The purpose of this study was to find out the stastisticts and kind of drug interactions hospitalized in Dr. Kariadi Hospital Semarang for cervix uteri cancer in 2007. This study was a non-experimental research conducted retrospectively. The research was implemented to the medical records for cervix uteri cancer patients hospitalized in Dr. Kariadi Hospital Semarang. Data obtained were analysed with descriptive non-analytic method. The result of this study showed that 96 in-patients of cervix uteri cancer, 55 patients (57,29 %) had drug interactions, while 41 patients (42,7 %) had not drug interactions. From a total number of 149 cases, 134 cases (89,93 %) had drug interaction, while 15 cases (10,07 %) had not drug interaction. Based on the types of interactions, 6 patients (4,48%) had pharmakokinetic interactions and the other 128 patients (95,52 %) had unknown mechanism drug interactions. The most drugs producing interactions were midazolam and propofol. Key words : Drug Interactions, Cervix Uteri Cancer, Cer, Dr. Kariadi Hospital.